Synthesis of ï§-Al2O3 Catalyst Support from Kaolin of Indonesian Origin - Samadhi, Tjokorde Walmiki; Subagjo, Subagjo; Lismana, Kevin R.; Fuadi, Khasin (Journal of Engineering and Technological Sciences, 2011)
KaolinÂ  hasÂ  beenÂ  identifiedÂ  asÂ  aÂ  potentialÂ  rawÂ  materialÂ  forÂ  the production ofÂ  ï§-Al2O3Â  forÂ  hydrotreatingÂ  catalyst support. This work explores the technicalÂ  feasibilityÂ  ofÂ  applyingÂ  theÂ  potassiumÂ  hydroxideÂ  (KOH)Â  e xtraction synthesis route on kaolinÂ  from the BelitungÂ  IslandÂ  in Indonesia. The application ofÂ  aÂ  publishedÂ  synthesisÂ  methodÂ  toÂ  BelitungÂ  kaolinÂ  requiresÂ  anÂ  approximately twofoldÂ  increaseÂ  inÂ  kaolinÂ  calcinationÂ  time,Â  anÂ  increaseÂ  inÂ  kaolinÂ  calcination temperature from 950 to 1000 Â°C, and a tenfold increase in metakaolin extraction time, to obtain a specific surface area higher than 200 m2/g. The highest specific surface area of 233 m2/g was obtained whenÂ  the kaolin was calcined at 1000 Â°C for 24 hours, and theÂ  metakaolinÂ  was extracted by concentrated KOHÂ  solution for 12 hours.Â  Phase characterization of the final product confirmed the formation of ï§-Al2O3, but with the inclusion of low-surface area ï¡-Al2O3 phase.